Genotypic and genomic characterization of pili-carrying clinical isolates of Streptococcus pneumoniae from two major tertiary hospitals in Malaysia - Dzaraly, Nurul Diana (2022)
Pili are detected in a small proportion of the pneumococcal population but the discovery of non-flagellar pili has recently been associated with pneumococcal pathogenesis in humans. The information regarding piliated isolates remains scarce, especially in terms of genomic studies undertaken in Malaysia. Therefore, this study aimed to characterize a collection of pili-carrying and none pili-carrying pneumococcal isolates of clinical origin for serotypes, antibiotic resistance, genotyping and comparative whole-genome. In total, 142 clinical isolates were collected from Hospital Sultanah Nur Zahirah (HSNZ), Terengganu and Hospital Sungai Buloh (HSB), Selangor between August 2017 and December 2019. Those isolates were subjected to serotyping and antimicrobial susceptibility tests, detection of pneumococcal virulence and pilus genes. Multilocus sequence typing (MLST) and phylogenetic analysis were performed only for the piliated isolates, while selected invasive piliated isolates were subjected to whole-genome sequence analysis. Demographic analysis showed that pneumococcal infection was higher in males (57.7%) than females (42.3%), while most isolation sites were from sputum (35.2%), followed by blood (34.5%), eye (10.6%), tracheal aspirate (8.5%) and pus (5.6%). The most frequent were serotypes 6A/B (18.3%), 19F (16.2%), 14 (12.7%), 19A (12.0%), and 23F (9.2%), which were vaccine serotypes. Serotype 15B/C was the predominant non-vaccine serotype among the pneumococcal collections. Most isolates were resistant to erythromycin (44%), tetracycline (41%) and trimethoprimsulfamethoxazole (30%). Piliated isolates occurred in a proportion of 23.2%; 51.5% of them were multidrug-resistant (MDR) and the majority had serotype 19F. This study revealed that ST236 and ST320 were the predominant sequence types (ST) among the piliated isolates and were genetically related to the PMEN clones Taiwan19F-14 and CC271. ST236 was the most prevalent ST in HSNZ, while ST320 was the most common ST in HSB. Interestingly, three novels, ST15604, ST16430 and ST16499, were found among the piliated isolates. In the phylogenetic analysis, the piliated isolates were grouped into three major clades, supported by 100% bootstrap values. Seven invasive piliated pneumococcal isolates from HSNZ and HSB were subjected to whole-genome analysis. The genomic content of all the piliated isolates was diverse, with the presence of various mobile genetic elements (MGEs) such as phage and insertion sequence, as well as virulence factors and resistance determinants. In-silico MLST, five different STs were reported; ST236, ST320, ST386, ST671 and ST695. Overall, a BLAST search identified two major variants of the PI-1 and PI-2 genes, which were conserved with minor mutations within the variant’s groups. Core genome analysis of all the representative piliated isolates and another 35 global references formed three major clades. An interesting observation was that the piliated isolates; TSP95, SSP45 and SSP46 were closely related to the South Korea strains, indicating their long persistence over more than a decade. They may have evolved and be descended from the South Korea international clones. TSP106 from clade III was grouped into a strain with the same geographical origin as the Malaysian strains. Thus, this analysis provided insights into the characteristics of piliated isolates in the Malaysian context and showed that they are related to resistance determinants and ST. Therefore, continuing the surveillance, prevention and control of S. pneumoniae in this region can be regarded as important.